Lysophospholipid (S1P) receptors (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database. (2020) - Blaho, Victoria; Chun, Jerold; Jones, Danielle; Jonnalagadda, Deepa; Kihara, Yasuyuki; Tan, Valerie
No abstract available